Detection of multiple tick-borne pathogens in Ixodes scapularis from Hunterdon County, NJ, USA - Zoe E. Narvaez; Tadhgh Rainey; Rose Puelle; Arsala Khan; Robert A. Jordan; Andrea M. Egizi; Dana C. Price (Current Research in Parasitology and Vector-Borne Diseases, 2023)
Several human pathogens vectored by the blacklegged tick (Ixodes scapularis Say; Acari: Ixodidae) are endemic in the state of New Jersey. Disease incidence data suggest that these conditions occur disproportionately in the northwestern portion of the state, including in the county of Hunterdon. We conducted active surveillance at three forested sites in Hunterdon County during 2020 and 2021, collecting 662 nymphal and adult I. scapularis. Ticks were tested for five pathogens by qPCR/qRT-PCR: Anaplasma phagocytophilum, Babesia microti, Borrelia burgdorferi, Borrelia miyamotoi, and Powassan virus (POWV) lineage 2. Over 2 years, 25.4% of nymphs and 58.4% of adults were found infected with at least one pathogen, with 10.6% of all ticks infected with more than one pathogen. We report substantial spatial and temporal variability of A. phagocytophilum and B. burgdorferi, with high relative abundance of the human-infective A. phagocytophilum variant Ap-ha. Notably, POWV was detected for the first time in Hunterdon, a county where human cases have not been reported. Based on comparisons with active surveillance initiatives in nearby counties, further investigation of non-entomological factors potentially influencing rates of tick-borne illness in Hunterdon is recommended.